2013
DOI: 10.1038/cddis.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic transcription factor Brachyury blocks cell cycle progression and mediates tumor resistance to conventional antitumor therapies

Abstract: The T-box transcription factor Brachyury, a molecule frequently detected in human cancers but seldom found in normal adult tissue, has recently been characterized as a driver of the epithelial-to-mesenchymal switch of human carcinomas. In the current investigation, we present data demonstrating that in two different human lung carcinoma models expression of Brachyury strongly correlates with increased in vitro resistance to cytotoxic therapies, such as chemotherapy and radiation. We also demonstrate that chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 42 publications
4
83
0
Order By: Relevance
“…Moreover, depletion of Brachyury in chordoma cells promotes a complete block of cell proliferation (41). An opposite role for Brachyury in cell proliferation was demonstrated in lung and colorectal cell lines by Huang and collaborators, where Brachyury blocks cell cycle progression and mediates tumor resistance to conventional antitumor therapies (15). Therefore, it can be deduced that the role of Brachyury may be tissue-specific or cell-type-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, depletion of Brachyury in chordoma cells promotes a complete block of cell proliferation (41). An opposite role for Brachyury in cell proliferation was demonstrated in lung and colorectal cell lines by Huang and collaborators, where Brachyury blocks cell cycle progression and mediates tumor resistance to conventional antitumor therapies (15). Therefore, it can be deduced that the role of Brachyury may be tissue-specific or cell-type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported divergent effects of Brachyury expression on cell proliferation. In lung cancer cell lines, it was demonstrated that Brachyury blocks cell-cycle progression and, therefore, mediates tumor resistance (15). However, in adenoid cystic carcinoma cells, Brachyury promoted tumor growth and metastasis formation in vivo (11).…”
Section: Introductionmentioning
confidence: 99%
“…Brachyury involvement in cancer was initially limited to chordomas, being currently its main etiological factor [14]. More recently, it has been associated with tumor aggressiveness in several types of cancer cells, ultimately promoting invasion and metastasis [15][16][17][18][19][20][21][22]. Our group has recently described Brachyury as a new and important marker of poor prognosis, cell invasion and metastasis in prostate cancer patients, where it was also associated with higher EMT and stemness expression profiles [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Brachyury was demonstrated to induce EMT in human epithelial cells through induction Snail, Slug, and downstream signal [20]. An earlier study on human lung carcinoma cells (in vitro and in vivo) has demonstrated that overexpressed Brachyury divides at slower rates than those with lowexpressed Brachyury, a phenomenon associated with marked downregulation of cyclin D1, phosphorylated Rb, and CDKN1A (p21) [21]. Another study on oral squamous cell carcinoma cells demonstrated that the expression of Brachyury was correlated with EMT and was significantly associated with lymph node and distant metastasis [22].…”
Section: Introductionmentioning
confidence: 99%